Radios libres: le point de vue anglais - Lewis, Peter M. (L'Harmattan, 2016)
The radios libres which broke state broadcasting monopolies in the 1970s in Italy, France and Belgium tantalised the British community radio movement with their radiophonic virtuosity, intellectual critique and political engagement. Although the rhetoric of British community radio activists drew on many sources in Europe and from the USA and Australia, it was to be many years before community radio in any legal form was heard on the British airwaves.